Prevalence and Clinical Characteristics of Mycobacterial Diseases in the Barletta-Andria-Trani Province, Italy (2005–2013). (17th January 2016) - Brindicci, Gaetano; Santoro, Carmen Rita; Trillo, Giovanna; Volpe, Anna; Loconsole, Daniela; Monno, Laura; Fontana, Tommaso
Abstract : Tuberculosis remains one of the major worldwide problems regarding public health. This study evaluates the burden of this disease in the BAT Province of the Apulia region (Italy); 12, 295 patients were studied, including 310 immigrants. Tubercular disease and mycobacteriosis were found in 129 patients. The number of new TB cases/year ranged from three in 2005 to 12 in 2009. TB was more frequently localized in the lung (70.5%). 14.4% of cases were institutionalized patients for severe neurological and/or psychiatric disease. The database evidenced certain aspects of our study population: the large number of TB patients institutionalized between natives, but no larger presence of TB among HIV-positive patients in immigrants compared to Italians. Our findings should help to redefine the alarm regarding the spread of an epidemical form of TB but also to present certain criticisms regarding patient management (especially immigrants) regarding costs, hospitalization, and difficulty of reinstating the patient in the community. Further our data underscore the importance of prevalence of TB in bedridden, institutionalized patients.